Polarization of climate politics results from partisan sorting: Evidence from Finnish Twittersphere - Chen, Ted Hsuan Yun; Salloum, Ali; Gronow, Antti; Ylä-Anttila, Tuomas; Kivelä, Mikko (Global environmental change, 2021)
•Alignment between political issues is an important part of political polarization.•Preferences toward climate politics and immigration politics are strongly aligned.•Issue alignment is limited to specific domains in the Finnish multiparty system.•Partitioned Twitter network data reveals positions toward political issues.•Normalized Mutual Information suitably measures alignment of political cleavages. Prior research shows that public opinion on climate politics sorts along partisan lines. However, they leave open the question of whether climate politics and other politically salient issues exhibit tendencies for issue alignment, which the political polarization literature identifies as among the most deleterious aspects of polarization. Using a network approach and social media data from the Twitter platform, we study polarization of public opinion toward climate politics and ten other politically salient topics during the 2019 Finnish elections as the emergence of opposing groups in a public forum. We find that while climate politics is not particularly polarized compared to the other topics, it is subject to partisan sorting and issue alignment within the universalist-communitarian dimension of European politics that arose following the growth of right-wing populism. Notably, climate politics is consistently aligned with the immigration issue, and temporal trends indicate that this phenomenon will likely persist.